An optimization study for bio-removal of lead from aqueous environments by alkali modified Polyporus Squamosus - Ümit Ecer; Tekin Şahan; Şakir Yılmaz (MANAS: Journal of Engineering)
Rapidly increasing industrialization and urbanization cause serious environmental pollution. Discharge of polluting material from various industries such as smelting, mining, ore processing, and metal plating into the environment without treatment causes serious pollution and can have dangerous effects on the environmental balance. The utilization of low-cost adsorbents from biological materials as a replacement for costly traditional methods for adsorption of heavy metal pollutants from wastewater was reviewed. This study aimed to investigate the biosorption of Pb(II) ions from aqueous solutions with NaOH-modified Polyporus squamosus biosorbent and optimize the biosorption conditions. Firstly, the parameters most influencing the response of the biosorption for Pb(II) (initial Pb(II) concentration (Co), pH, temperature and biomass dose) were determined using Central Composite Design (CCD). The optimum conditions were evaluated as 60.76 mg/L, 6.3, 25 °C, and 0.23 g for Co, initial pH, temperature and biomass dose, respectively. From the optimum conditions, the adsorption yield and the adsorption capacity were obtained as 93.8% and 23.63 mg/g, respectively.